Acute effects on human sperm exposed in vitro to cadmium chloride and diisobutyl phthalate. Issue 3 (September 2019) - Marchiani, S; Tamburrino, L; Farnetani, G; Muratori, M; Vignozzi, L; Baldi, E
Abstract : Epidemiological studies reported a negative relationship between concentrations of heavy metals and phthalates in seminal fluid and semen quality, likely compromising male fertility potential. The aim of this study was to investigate the in vitro effects of cadmium chloride (CdCl2 ), a common heavy metal, and diisobutyl phthalate (DIBP), a common phthalate ester, on human sperm functions necessary for fertilization. After in vitro incubation of spermatozoa with 10 µM CdCl2 or 100 and 200 µM DIBP for 24 h, a significant decrease of sperm progressive and hyperactivated motility was observed. The exposure to each of the two toxic agents also induced spontaneous sperm acrosome reaction and blunted the physiological response to progesterone. Both agents induced an increase of caspase activity suggesting triggering of an apoptotic pathway. Our results suggest that acute exposure of spermatozoa to these pollutants may impair sperm ability to reach and fertilize the oocyte.